Growth Performance and Nutrient Composition of Mustard Green (Brassica juncea) cultured in Aquaponics Systems and Hydroponic System - Prayogo Prayogo; Agustono Agustono; Boedi Setya Rahardja; Muhamad Amin (Department of Aquaculture, 2021)
Aquaculture waste is rich in various nutrient contents from uneaten feed, faeces or urine including nitrogen in terms of total ammonium nitrogen (TAN) and nitrite. With the help of nitrifying bacteria, the nitrogen wastes can be converted into nitrate which is one of the main components of commercial fertilizer in agriculture. This study aimed at comparing the growth and nutrient contents (crude protein, crude fat, energy, and antioxidant) of mustard Green (Brassica juncea) cultured in different culture media (aquaculture waste which is generally known as the aquaponics system vs hydroponic system which used commercial inorganic fertilizer). The aquaponics system was prepared by previously growing Nile tilapia fingerling, Oreochromis niloticus, for 2 weeks to reach nitrate concentration on the effluent water 30mg/L. Mustard Green was cultured in the system for 30 days. Nutrient availability in both systems was also monitored by measuring nitrate content and total dissolved solids. The results showed that the growth, nutrient content including crude protein, crude fat, total energy, and antioxidant content of the vegetable were not significantly different between the system, p>0.05. Nutrient availability especially in terms of nitrate was also not significantly different between the culture system. These results suggest that the aquaponics system could be used to produce vegetables with the same growth and nutrient content as a vegetable grown in the aquaponics system. Furthermore, aquaculture waste can be used to replace inorganic fertilizer to grow vegetables which later contribute to the reduction of total production cost.